ON THE EVOLUTIONARY HISTORY OF PROGENITORS OF EHBS AND RELATED BINARY SYSTEMS BASED ON ANALYSIS OF THEIR OBSERVED PROPERTIES - Pustynski, V. -V.; Pustylnik, I. (Одеські астрономічні публікації, 2007)
It has been shown quite recently (Morales-Rueda et al., 2003) that dB stars, extreme horisontal branch (EHB) objects in high probability all belong to binary systems. Assuming that the progenitors of EHB objects belong to the binaries with initial separations of a roughly a hundred solar radii and fill in their critical Roche lobes when being close to the tip of red giant branch, we have found in our earlier study that considerable shrinkage of the orbit can be achieved due to a combined effect of angular momentum loss from the red giant and appreciable accretion on its low mass companion on the hydrodynamical timescale of the donor, resulting in formation of helium WD with masses roughly equal to a half solar mass and thus evading the common envelope stage. Far UV upturn phenomenon discovered in elliptical galaxies and spiral galaxy bulges was interpreted in terms of predominant contribution from EHB objects (Dorman, O'Connell, Rood, 1995). This circumstance can provide a reasonable constraint on the initial masses of EHB progenitors and thus the ages of EHB objects.